False memory and age : a review on false memory susceptibility in children and the elderly - Chen, Zhi Xin (2014)
People of any age are susceptible to false memories. In the legal scene, false memories have led to many eyewitness misidentifications and wrongful convictions. In order to minimize the risks of false memories, it is important to understand who is more susceptible and why that is so. We hypothesized that children and the elderly are most susceptible to false memories due to compromised cognitive functioning in these two populations. We reviewed existing literature in false memory research, focusing specifically on children (aged 3-17) and the elderly (aged 60 and above). Age differences in false memory susceptibility were examined across a wide variety of measures and were explained by three prominent theories: schema theory, source-monitoring framework and fuzzy-trace theory. We found that children’s susceptibility to false memories was dependent on the type of task. On tasks that involved leading questions, implausible events and reality-monitoring, younger children were most susceptible to false memories, followed by older children and adolescents. However, they were less susceptible to false memories on tasks that required them to form meaning-associations. On the other hand, we found that the elderly were more susceptible to false memories as compared to adults. Their vulnerability was observed on tasks that required them to form meaning-associations and monitor source memories. Finally, possible methods to reduce false memories for both children and the elderly were suggested.